2014
DOI: 10.1093/aje/kwu089
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Fiber and Amyotrophic Lateral Sclerosis: Results From 5 Large Cohort Studies

Abstract: Amyotrophic lateral sclerosis (ALS) is a fast-progressing neurodegenerative disease with a median survival time from diagnosis of 1.5-3 years. The cause of ALS is unknown, but inflammation may play a role. Fiber has been shown to lower inflammatory markers, and a high fiber intake was associated with a lower risk of ALS in a case-control study; however, prospective studies are lacking. We explored the relation between dietary intake of fiber and the risk of ALS in 5 large prospective cohort studies comprising … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
3
0
1
Order By: Relevance
“… 67 Comparing outcomes from five large cohort studies, no change in ALS risk relative to dietary fiber intake was observed. 68 Of interest, a diet rich in antioxidant nutrients, carotenoids and fiber, and vegetables is associated with improved function in ALS patients. 69 Whether improved function was due to increased fiber intake was not specifically addressed.…”
Section: Dietary Interventions That Address Reduced Appetite and Digementioning
confidence: 99%
“… 67 Comparing outcomes from five large cohort studies, no change in ALS risk relative to dietary fiber intake was observed. 68 Of interest, a diet rich in antioxidant nutrients, carotenoids and fiber, and vegetables is associated with improved function in ALS patients. 69 Whether improved function was due to increased fiber intake was not specifically addressed.…”
Section: Dietary Interventions That Address Reduced Appetite and Digementioning
confidence: 99%
“…Although there are foods that seem to predispose to the onset of ALS due to the release of ROS, there are also foods and compounds that might be able to prevent the disease and slowing its course [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sin embargo, en este análisis se ha observado una ingesta de fibra deficiente lo que se podría relacionar con que el 84,62% de los pacientes (11 sujetos) padecían constipación. Resultados similares se han obtenido en otros estudios que determinaron una asociación inversamente proporcional entre la ingesta de fibra dietética y el riesgo de ELA 32 . Otra investigación que analizó la ingesta de fibra en 272 pacientes con ELA, determinó una relación negativa entre su consumo y factores inflamatorios en el líquido cefalorraquídeo.…”
Section: Discussionunclassified